Rational development of Stafib-2: a selective, nanomolar inhibitor of the transcription factor STAT5b - Nagarajan Elumalai (Nature Portfolio, 2017)
Abstract The transcription factor STAT5b is a target for tumour therapy. We recently reported catechol bisphosphate and derivatives such as Stafib-1 as the first selective inhibitors of the STAT5b SH2 domain. Here, we demonstrate STAT5b binding of catechol bisphosphate by solid-state nuclear magnetic resonance, and report on rational optimization of Stafib-1 (Ki = 44 nM) to Stafib-2 (Ki = 9 nM). The binding site of Stafib-2 was validated using combined isothermal titration calorimetry (ITC) and protein point mutant analysis, representing the first time that functional comparison of wild-type versus mutant protein by ITC has been used to characterize the binding site of a small-molecule ligand of a STAT protein with amino acid resolution. The prodrug Pomstafib-2 selectively inhibits tyrosine phosphorylation of STAT5b in human leukaemia cells and induces apoptosis in a STAT5-dependent manner. We propose Pomstafib-2, which currently represents the most active, selective inhibitor of STAT5b activation available, as a chemical tool for addressing the fundamental question of which roles the different STAT5 proteins play in various cell processes.